Hybrid Learning Management in Islamic Education in the Digital Age: Challenges to Traditional Methods and Transformative Solutions - Umayyatun Umayyatun; Ludfi Ludfi (Universitas Nurul Jadid, 2025)
The rapid advancement of digital technology has fundamentally transformed the landscape of education globally, including Islamic educational institutions. This study examines the management challenges and transformative strategies associated with implementing hybrid learning in Islamic education during the digital age. Employing a systematic literature review methodology, this research synthesizes findings from 25 peer-reviewed journal articles published between 2018 and 2024. The study identifies three primary categories of challenge: the tension between technology integration and the preservation of classical pedagogical traditions (tarbiyah and ta'lim), inadequate digital infrastructure in Islamic boarding schools (pesantren) and madrasah, and the limited digital literacy among educators and religious scholars (ustadz/ustadzah). Findings reveal that transformative management solutions encompass the adoption of blended Islamic curriculum frameworks, digital leadership capacity building for school administrators, and the strategic integration of e-learning platforms with traditional halaqah and kitab learning methods. The study concludes that hybrid learning, when managed through an Islamic educational management lens, can enhance both academic outcomes and the spiritual-moral formation of students. Institutional policy reforms, collaborative stakeholder engagement, and value-aligned technology adoption are proposed as pillars of sustainable hybrid learning management in Islamic educational contexts.